2009
DOI: 10.1080/08977190903112663
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone supplementation increased latency to tumourigenesis inAtm-deficient mice

Abstract: Growth hormone (GH) is important for cell growth and differentiation, has multiple effects on lymphoid tissue and may promote blast cell proliferation and cancer development. We studied the effect of GH on longevity and tumour formation in Atm-deficient mice, an established model of the human cancer prone syndrome ataxia telangiectasia (AT). AT is a devastating recessive disorder that is characterized by progressive cerebellar ataxia, immunodeficiency, chromosomal instability and cancer susceptibility. Since A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Indeed, treatment with IGF-1 has proven effective in animal models of ataxia [16,37]. Recently, we could show that supplementation with GH significantly increased longevity of ATM-deficient mice and improved T-cell immunity and locomotor behavior [42]. Based on these reports we propose that a trial of GH/IGF-1 therapy might be justified in those patients where either serum IGF-I deficiency or loss of sensitivity to GH is present.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, treatment with IGF-1 has proven effective in animal models of ataxia [16,37]. Recently, we could show that supplementation with GH significantly increased longevity of ATM-deficient mice and improved T-cell immunity and locomotor behavior [42]. Based on these reports we propose that a trial of GH/IGF-1 therapy might be justified in those patients where either serum IGF-I deficiency or loss of sensitivity to GH is present.…”
Section: Discussionmentioning
confidence: 94%
“…In this regard, our findings of low IGF-1 levels in AT could reflect a protective effect that inhibits possible tumor growth. Interestingly, we recently showed that GH treatment is safe and that it significantly increased the longevity of Atmdeficient mice (Schubert et al, 2009). In addition, GH treatment was effective and safe in inflammatory diseases such as cystic fibrosis and has been occasionally used in other genomic instability syndromes, such as Fanconi anemia and Seckel syndrome (Birkebaek et al, 2011;Casper et al, 2004;Pozzo & Kemp, 2012;Stahnke, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…While the pathogenic significance of IGF-1 in A-T is difficult to envisage, disrupted IGF-1 neuroprotective signalling may constitute a common stage in the pathological cascade associated with neuronal death (Hoche et al, 2012). Indeed, treatment with IGF-1 has been effective in animal models of ataxia (Schubert et al, 2009;Tolbert & Clark, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…In our study, we investigated a pathogen-independent damage in order to determine differences in host mucosal inflammatory and repair mechanisms in Atm -/- mice in comparison to control mice. Interestingly, Atm -/- mice did not show any clinical symptoms except for smaller size at birth and a slower growth rate compared to the wild-type littermates [34]. However, when challenged with hydrochloric acid, causing a disruption in the integrity of the airway epithelial barrier, we showed that Atm -/- mice exhibit greater severity of clinical symptoms and mortality rates as well as airway recruitment of peripheral leukocytes, and mount an even stronger immune response characterized by inflammatory biomarkers compared with wild-type mice.…”
Section: Discussionmentioning
confidence: 99%